P153 Using information technology to improve linkage into sexual health care in patients receiving hiv post exposure prophylaxis for sexual exposure (PEPSE) in emergency departments. (8th June 2017) - Metcalfe, Rebecca; Gaughan, Claire; Kilmurray, Kim; Carroll, Louise; Pollock, Kay; Murchie, Martin; Smith, Hannah
Abstract : Introduction: HIV PEPSE should be commenced within 72 hours (ideally 24) after possible exposure to HIV. Patient education on PEPSE includes advice on attendance at Emergency Department (ED) if outside opening hours of local sexual health services (SHS). Our healthboard serves a population of 1.2 million with four EDs. An initial four month audit revealed 12 patients who received a 5-day starter pack of PEPSE at ED and no communication between departments; patients were told to self-refer to SHS. We recognised there was no robust mechanism to ensure these high risk patients were not lost to follow up (LTFU). HIV testing at baseline was also poor in this setting, highlighting importance of linkage into SHS. Methods: HIV PEPSE 5 day pack leaflets were altered to ask the dispensing clinican to refer patient via secure email or telephone message to the sexual health advisers. Results: Prospective four month re-audit revealed 19 patients attended ED for PEPSE and all subsequently attended SHS for follow up(100%). 12/19(63%) were referred by email, 6/19(32%) via answering machine, 1/19(5%) self referred. 11/19(60%) reported unprotected receptive anal intercourse with someone from a high risk group. Discussion: Following implementation of the email/telephone referral intervention, we found an increased number of patients received HIV PEPSE from EDs in the health board area and all were successfully linked into sexual health services. We cannot be sure that this increase is due to the prevention of patients being LTFU; other reasons include an increased awareness of PEPSE and where to obtain.